The Impact of Organizational on the Achievement Index - Akbarti Na'ima; Nasikh; Grisvia Agustin (International Journal of Economics and Management Research, 2022)
In addition to studying, students choose to study while participating in organizing activities to fill their free time. However, the joining of students in organizations has both positive and negative impacts. The Achievement Index (IP) can be used as a benchmark for the maturity of a student's cognitive abilities. Researchers use qualitative methods with a phenomenological approach. The determination of informants uses purposive sampling with the criteria for students majoring in Development Economics (EKP) UM class of 2018 who follow the organization. Data collection was carried out with in-depth interviews and documentation. The results of the study found several findings, namely students majoring in EKP 2018 have IP in the good category above 3.50 and have increased when participating in organizations, but among them have experienced a decrease, but not significant. Students have also been and often are not present in lectures on dispense grounds. Other impacts beyond academic achievement include gaining a lot of experience, gaining relationships, mastering public speaking, understanding various backgrounds of people, knowing how to work in a team, and experiencing the external experience of the campus